A chromosome 1q44 deletion in a 4-month-old girl; The first report in Korea - Joo Hyun Cho; Eun Song Song; Hee Na Kim; Burm Seok Oh; Young Youn Choi (Korean Pediatric Society, 2014)
The deletion of the distal long arm of chromosome 1 is associated with a characteristic facial appearance and a pattern of associated malformations. Characteristic manifestations include a round face with prominent 'cupid's bow' and downturned corners of the mouth, thin vermilion borders of lips, a long upper lip with a smooth philtrum, a short and broad nose, epicanthal folds, apparently low-set ears, micrognathia, microcephaly, abnormal hands and feet, variable cardiac or genital anomalies, moderate to severe mental retardation, and growth retardation. Using fluorescent in situ hybridization (FISH) analysis to map precisely the deletion, we present a case of chromosome 1q44 deletion with craniofacial characteristics, multiple congenital anomalies, and growth and psychomotor retardation. In comparison with other reported cases of 1q43-44 deletion, the subject does not show hydrocephalus, seizure, syn- or polydactyly of hands, and a urogenital anomaly. However, an arachnoid cyst, pinpoint dimple on the midline of the forehead, a right-sided supernumerary nipple and auricular pit, polydactyly of the right foot, adducted thumb, and flexion restriction of the proximal interphalangeal joint with a simian line in both hands were observed additionally.